2017
DOI: 10.5489/cuaj.4668
|View full text |Cite
|
Sign up to set email alerts
|

Urologist burnout: Frequency, causes, and potential solutions to an unspoken entity

Abstract: IntroductionPhysician burnout has been linked to decreased job performance, increased medical errors, interpersonal conflicts, and depression. Recent multispecialty studies suggest that urologists have higher rates (up to 63.6%) of burnout compared to physicians in other specialties; however, these reports were limited by low sample sizes. We aimed to evaluate the prevalence of urologist burnout, verify risk factors, and recommend preventative measures and solutions for colleagues at risk or suffering from bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…In general, surgeons are already at higher risk of burnout, 27,28 with recent multispecialty studies showing urologists with some of the highest rates among medical specialties. 29,30 Consequently, young investigators grapple with the additional stresses of running a lab and finding funding while facing the constant need to increase productivity and costeffectiveness. Career advancement is complicated by limits from specialty journals on basic and translational science content, inhibiting the publication and dissemination of findings.…”
Section: Discussionmentioning
confidence: 99%
“…In general, surgeons are already at higher risk of burnout, 27,28 with recent multispecialty studies showing urologists with some of the highest rates among medical specialties. 29,30 Consequently, young investigators grapple with the additional stresses of running a lab and finding funding while facing the constant need to increase productivity and costeffectiveness. Career advancement is complicated by limits from specialty journals on basic and translational science content, inhibiting the publication and dissemination of findings.…”
Section: Discussionmentioning
confidence: 99%
“…Are they dissuaded by the high rates of burnout in urology ? 9 Are the demands of training and work hours undesirable for females? Is it possible that female medical students are not gaining enough exposure to urology during their clerkship year?…”
Section: Discussionmentioning
confidence: 99%
“…Though there is huge medical research and increased awareness about burnout, still the incidence of burnout amongst doctors continues to climb. 11 One of the largest studies, involving more than 35,000 physicians in the United States, revealed 10% rise in burnout and 8% decline in the satisfaction of work-life balance (WLB) in 2014 as compared to 2011 studies. 12 Urologists had high rate of burnout (67%) and lower satisfaction rates.…”
Section: Discussionmentioning
confidence: 99%
“…When more than one third of surgeons experience burnout and low job satisfaction, there is a risk of losing a major component of our work force to early retirement and potential substance abuse which could adversely affect the quality of care provided to patients across the medical spectrum 11 . Today young urologists are more stressed and burnout permeates our medical culture as early as residency training and continues to be a major factor in job dissatisfaction, interpersonal conflicts and substance abuse even for urologists who are well into their senior years of practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation